Effect of the Keratinized Mucosa Width on the Health Status of Periimplant and Contralateral Periodontal Tissues: A Cross-sectional Study. Issue 6 (December 2016) - Ueno, Daisuke; Nagano, Takatoshi; Watanabe, Tsuneaki; Shirakawa, Satoshi; Yashima, Akihiro; Gomi, Kazuhiro
Abstract : Introduction: The purpose of this study was to examine whether the width of keratinized mucosa (WKM) is associated with the health status of tissue surrounding dental implants and the contralateral teeth. Materials and Methods: Sixty patients who received implant-fixed unilateral prostheses in the premolar or molar region were recruited for the study. The following parameters were measured for each implant and contralateral tooth: WKM, gingival index (GI), probing pocket depth (PPD), bleeding on probing (BOP), pus discharge, plaque accumulation (PA), gingival recession (GR), and difficulty of brushing. The effect of the WKM on the health status of the surrounding tissue was evaluated by comparing the different WKM groups (WKM < 2 mm vs WKM ≥ 2 mm). Results: Implants with a WKM <2 mm demonstrated significantly greater PPD, PA, and a higher rate of BOP compared with implants with a WKM ≥2 mm. There was significantly greater GR in contralateral teeth with a WKM <2 mm compared with a WKM ≥2 mm. In addition, implant sites had a higher rate of BOP compared with the contralateral teeth. Conclusions: Inadequate keratinized mucosa decreased cleansibility of implant sites and increased mucosal inflammation. There is a possibility that PA in implant sites caused more pronounced inflammatory response compared to contralateral tooth.